2006
DOI: 10.1111/j.1468-0122.2006.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Help‐Seeking and Young People: A Review

Abstract: In the United Kingdom, the issue of health and social care of young people is now a major concern for the government. Thus, a recent government green paper has insisted on the provision of early and appropriate interventions for young peoples' mental health difficulties and that their views must be incorporated into the design of mental health services. More recently, the NHS Health Advisory Service has recommended that schools and teachers should assume some responsibility in the identification of pupils who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 81 publications
2
64
0
Order By: Relevance
“…Problems with interpreting, managing, and communicating distress can result in young men becoming caught in a cycle of avoidance as reported by Biddle et al (2007); often, waiting until severely distressed before seeking help (Cleary, 2012;Oliver, Pearson, Coe, & Gunnell, 2005). Perceived stigma is one of the most frequently cited barriers to professional help seeking in research literature (Clement et al, 2015;Rothì & Leavey, 2006); yet there is a lack of research exploring how young men experience stigma. Some studies have reported that young men may experience discomfort, embarrassment, fear, and shame around asking for help (Booth et al, 2004;Gonzalez et al, 2005;Hernan et al, 2010;Jorm, 2000;Rickwood et al, 2005).…”
Section: Barriers To Help Seeking For Young Menmentioning
confidence: 99%
See 1 more Smart Citation
“…Problems with interpreting, managing, and communicating distress can result in young men becoming caught in a cycle of avoidance as reported by Biddle et al (2007); often, waiting until severely distressed before seeking help (Cleary, 2012;Oliver, Pearson, Coe, & Gunnell, 2005). Perceived stigma is one of the most frequently cited barriers to professional help seeking in research literature (Clement et al, 2015;Rothì & Leavey, 2006); yet there is a lack of research exploring how young men experience stigma. Some studies have reported that young men may experience discomfort, embarrassment, fear, and shame around asking for help (Booth et al, 2004;Gonzalez et al, 2005;Hernan et al, 2010;Jorm, 2000;Rickwood et al, 2005).…”
Section: Barriers To Help Seeking For Young Menmentioning
confidence: 99%
“…Moreover, research on facilitators to professional help seeking is limited (Gulliver, Griffiths, & Christensen, 2010) with most research simply suggesting the mitigation of the barriers identified (Rothì & Leavey, 2006). However, an important finding on facilitators has shown young people need to have established and trusted relationships with those who can offer help (Rickwood et al, 2007;Vogel et al 2007).…”
Section: Rationalementioning
confidence: 99%
“…Recent reviews (Abbott et al 2004;Delfabbro and LeCouteur 2003) indicate that there is a paucity of research on barriers to treatment for problem gambling. These reviews did not locate any published studies focusing specifically on family members of problem gamblers, yet families are thought to be significant pathways to help-seeking (Rothi and Leavey 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Ideally, mental health care should be available, in some form, in a school context and/or mental health services should take direct referrals from schools (WHO, 2000;Rothi & Leavey 2006a). In the absence of this, commissioning of gatekeeping training should take place concurrently with the auditing of existing provision and protocols in care pathways for young people at risk of suicide.…”
Section: Discussionmentioning
confidence: 99%